1994
DOI: 10.1084/jem.180.6.2309
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of c-ets/PU.1 and c-myb protooncogene products in regulating the macrophage-specific promoters of the human and mouse colony-stimulating factor-1 receptor (c-fms) genes.

Abstract: The receptor for macrophage colony stimulating factor (CSF-1), the c-fms gene product, is a key determinant in the differentiation of monocytic phagocytes. Dissection of the human and mouse c-fms proximal promoters revealed opposing roles for nuclear protooncogenes in the transcriptional regulation of this gene. On the one hand, c-ets-1, c-ets-2, and the macrophage-specific factor PU.1, but not the ets-factor PEA3, trans-activated the c-fms proximal promoter. On the other hand c-myb repressed proximal promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 46 publications
6
88
1
Order By: Relevance
“…Because induction of terminal differentiation is associated with growth arrest and more mature macrophage cell lines express higher levels of mDEP-1 mRNA, the expression of mDEP-1 was examined in M1 (a myeloid precursor cell line) cells, which respond to leukemia inhibitory factor (LIF) or interleukin 6 with growth arrest and expression of macrophage-specific genes. As observed previously, addition of LIF to M1 cells caused differentiation to a macrophage-like cell with the induction of c-fms, the CSF-1 receptor, occurring after day 2 [19]. Levels of mDEP-1 RNA were up-regulated within 24 h of LIF treatment and remained constant thereafter (Fig.…”
Section: Regulation Of Mdep-1 Mrna In Macrophagessupporting
confidence: 57%
“…Because induction of terminal differentiation is associated with growth arrest and more mature macrophage cell lines express higher levels of mDEP-1 mRNA, the expression of mDEP-1 was examined in M1 (a myeloid precursor cell line) cells, which respond to leukemia inhibitory factor (LIF) or interleukin 6 with growth arrest and expression of macrophage-specific genes. As observed previously, addition of LIF to M1 cells caused differentiation to a macrophage-like cell with the induction of c-fms, the CSF-1 receptor, occurring after day 2 [19]. Levels of mDEP-1 RNA were up-regulated within 24 h of LIF treatment and remained constant thereafter (Fig.…”
Section: Regulation Of Mdep-1 Mrna In Macrophagessupporting
confidence: 57%
“…Ets family transcription factors, particularly the macrophage-specific factor PU.1, have been ascribed in control of many macrophage-specific genes. 90,100,101 Targeted disruption of the PU.1 gene also causes osteopetrosis and failure of the osteoclast differentiation. 117 In keeping with such a role, we found that the TRAP promoter can be transactivated in transfections of the macrophage cell line RAW264 by both PU.1 and Ets-2, and that the former factor acts through the conserved Ets element highlighted in Figure 2 (unpublished data).…”
Section: Trap Expression In Osteoclastsmentioning
confidence: 99%
“…Unlike Mitf, Myb appears not to be required as a positive regulator of melanocyte-speci®c genes during di erentiation since this process is initiated upon inactivation of Myb in the transformed cells. Alternatively, it is possible that v-Myb either subverts the role of c-Myb (or one of its homologues) by inhibiting positive regulatory e ects of c-Myb on melanocytespeci®c genes (some or all of which may also be regulated by Mitf) or is re¯ecting a negative in¯uence of c-Myb on di erentiation related genes; indeed, such a negative regulatory role for c-Myb has been demonstrated on the c-fms promoter in myelomonocytic cells (Reddy et al, 1994).…”
Section: C-myb In Relation To Other Transcription Factors Involved Inmentioning
confidence: 99%